THE EFFECT OF SERVICE QUALITY ON COMPLIANCE OF SME TAXPAYERS IN SUBANG REGENCY - Silvia Ayu Safitri; Daeng M. Nazier (Journal of Taxation Analysis and Review, 2021)
This study aims to determine whether service quality has a positive influence on the compliance of SME taxpayers (Micro, Small and Medium Enterprises). In this study, the sample was SME located in Subang Regency. The data processed from the questionnaire were 30 with the criteria of having an NPWP and being registered at the KPP Pratama Subang. The independent variable is service quality and taxpayer compliance as the dependent variable. The indicators on the independent variable are seen from direct evidence, reliability, responsiveness, assurance and empathy while the indicators of the dependent variable are registering, calculating, paying, and reporting. Data analysis in the study used simple linear regression analysis and hypothesis testing with SPSS. The results of this study indicate that service quality has a positive effect on SME taxpayer compliance in Subang Regency.